The Right to Health and the Social Determinants of Health in the Face of COVID-19. Tthe Spanish Experience after Austerity Policies - Carlos Lema Añón (Age of Human Rights Journal, 2021)
The COVID-19 pandemic has particularly affected Spain in 2020. Although the specific causes and Spain’s response—as well as the aspects to be improved—are yet to be evaluated, many experts agree that this crisis has magnified some of the problems of the Spanish health system, highlighting the problems derived from the cuts in the capacities of the health and public health systems. We assess the current situation from the perspective of the right to health in its twofold dimension: health care and social determinants. For this purpose, we look into the configuration of the right to health in Spain and how the economic crisis and austerity policies affected it. In particular, we consider the impact both on institutional health care systems and in terms of social determinants of health. Finally, we make several proposals for strengthening the right to health.